Evaluating the Impact of Medication Safety Alerts on Prescribing of Potentially Inappropriate Medications for Older Veterans in an Ambulatory Care Setting. (February 2017) - Vanderman, Adam J.; Moss, Jason M.; Bryan, William E.; Sloane, Richard; Jackson, George L.; Hastings, S. Nicole
Potentially inappropriate medications (PIMs) have been associated with poor outcomes in older adults. Electronic health record (EHR)-based interventions may be an effective way to reduce PIM prescribing. The main objective of this study was to evaluate changes in PIM prescribing to older adult veterans ≥65 years old in the ambulatory care setting preimplementation and postimplementation of medication alert messages at the point of computerized provider order entry (CPOE). Additional exploratory objectives included evaluating provider type and patient–provider relationship as a factor for change in PIM prescribing. A total of 1539 patients prealert and 1490 patients postalert were prescribed 1952 and 1897 PIMs, respectively. End points were reported as the proportion of new PIM orders of total new prescriptions. There was no significant difference in the rate of new PIMs prealert and postalert overall, 12.6% to 12.0% ( P = .13). However, there was a significant reduction in the rate of the top 10 most common newly prescribed PIMs, 9.0% to 8.3% ( P = .016), and resident providers prescribed fewer PIMs during both time periods. A simple, age-specific medication alert message during CPOE decreased the incidence of the most frequently prescribed PIMs in older adults receiving care in an ambulatory care setting.